Seasonal variation characteristics of fungi aerosol tracers in the northern Zhejiang Province - Xu, Honghui; Xu, Jingsha; He, Jun; Pu, Jingjiao; Qi, Bing; Du, Rongguang; Yu, Keai (Science Press, 2018)
One year-long PM2.5 field sampling was conducted at four representative sites in the Northern Zhejiang Province (NZP) from December 2014 to November 2015. Fungi aerosol tracers such as arabitol and mannitol have been measured by using high performance liquid chromatography (HPLC) -triple quadrupole tandem mass spectrometry (MS/MS). Seasonal variation characteristics and sources of fungal aerosol tracers in NZP area were studied. The annual averaged concentrations of arabitol and mannitol in NZP were (5.6 ± 0.7) and (5.7 ± 1.3) ng·m-3, respectively. The elevated fungal aerosol tracers in summer could be attributed to the intensive local biomass burning and effect of wet and warm weather conditions favorable for the release of fungal spores. The contributions of fungal spores to the organic carbon (OC), estimated using mannitol-based conversion factor, were below 1 % at all sampling sites. The results from principle component analysis (PCA) also showed that fungal spore tracers (arabitol, mannitol) and biomass burning tracers (levoglucosan, mannosan, galactosan, nss-K+) were mostly grouped within the same component contributing to PM2.5 mass during the whole sampling campaign, indicating a continuous influence from biomass burning to the airborne fungal spores in NZP.